The conduction mechanisms analysis of AlGaN/GaN MOSHEMTs with different source/drain electrode configurations - Canales, Bruno G. [UNESP]; Carmo, Genilson J. [UNESP]; Agopian, Paula G. D. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
In this work, an Al2O3/AlGaN/AlN/GaN metal oxide semiconductor high electron mobility transistor (MOSHEMT) is analyzed and the investigation of its conduction mechanisms is carried out considering different gate to source and gate to drain distances, as well as different source and drain contact depths. The devices can have up to 3 conduction channels, of which two of them are related to the 2DEG formation and one of them depends on field effect on MOS structure. While the HEMT conduction is more influenced by the source and drain contacts depth, the MOS conduction seems to be more affected by the gate to source and gate to drain distances. Each of these conductions influence the total drain current in a different way.
Keywords: 2deg; Algan; Aln; Double conduction mechanisms; Moshemt